Impact of Climate Change on Sea Surface Temperature and Chlorophyll-a Concentration in South Sukabumi Waters - Mamat Suhermat; Muhammad Dimyati; S. Supriatna; M. Martono (Jurnal Ilmu Lingkungan)
Indonesia territorial waters are very vulnerable to the impacts of climate change. Research about the variations of sea surface temperature and chlorophyll-a concentration in the southern waters of Java has been undertaken by several researchers. However, the research is still in the scope of regional scale south of Java. This research was conducted to determine the impact of climate change on sea surface temperature and chlorophyll-a concentration in Sukabumi waters. The data used consisted of IOD index anomalies, sea surface temperature and monthly chlorophyll-a concentrations from December 2002 to November 2020. Descriptive analysis was used to determine seasonal and inter-annual variability and linear regression method was used to analyze trends in changes in sea surface temperature (SST) and chlorophyll-a concentration. The results showed that the seasonal variation was influenced by the monsoon, while the interannual variation was influenced by the Indian Ocean Dipole. Climate change causes SST and chlorophyll-a concentrations to increase. In the 2003-2020 time period, SPL increased by 0.08 °C and an increase in chlorophyll-a concentration by 0.03 mg/ m3.